Influence of Fertilizers and Cultural Practices on the Incidence of Alternaria leaf Spot of Cluster Bean - Gaur, R B; Ahmed, Sheikh R; Bhari, N R (Annals of Arid Zone, 2016)
Incidence of Alternaria leaf spot of cluster bean decreased with the increase in nitrogen fertilizer. Minimum disease was recorded at 10 kg N and 20 kg P2O2 per hectare. Crop sown in last week of June escaped the disease and yielded more grains. Widely spaced planting exhibited more disease.